2014
DOI: 10.2105/ajph.2014.302116
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Parental Involvement Among Minors Seeking an Abortion: A Qualitative Study

Abstract: Minors were motivated to involve parents and other adults who were engaged in their lives at the time of the pregnancy, particularly those who supported them in obtaining an abortion. Motivations to exclude a parent were often based on particular family circumstances or experiences that suggested that involvement would not be helpful, might be harmful, or might restrict a minor's ability to obtain an abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 14 publications
3
49
0
Order By: Relevance
“…Similar to participants in other studies, the majority of young women had discussed their abortion decision with the male involved in the pregnancy. Building on Kimport and colleagues’ study of adult women, we found that participants desired both autonomy and social support in the decision‐making process.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similar to participants in other studies, the majority of young women had discussed their abortion decision with the male involved in the pregnancy. Building on Kimport and colleagues’ study of adult women, we found that participants desired both autonomy and social support in the decision‐making process.…”
Section: Discussionmentioning
confidence: 80%
“…However, even in the absence of parental involvement laws, most adolescents who decide to terminate a pregnancy involve a parent—most often their mother, who often supports their decision . When adolescents do not involve a parent, they report fear of their parents’ reactions to the pregnancy or termination, including violence, abandonment or being forced to continue the pregnancy . Yet, little is known about the type of social support received by adolescents who choose not to involve a parent in the decision to terminate a pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on these requirements has largely focused on their impact on the frequency and timing of abortion seeking among minors, and indicates that although these laws are associated with a reduction in in-state abortions [2][3][4][5][6][7][8], some minors will travel to a neighboring state where involvement is not required [3,4,6,7]. In addition, this research demonstrates that PI requirements are associated with increased delays in timing of abortion among minors [4,[9][10][11].…”
mentioning
confidence: 90%
“…10, 11 The specific requirements for parental consent is guided by laws; however, even in situations in which young adults have the legal right to make clinical decisions (e.g., abortion, vaccination), many still involve their parents in their decision making process. 12, 13 …”
Section: Introductionmentioning
confidence: 99%